Netiquette and its Necessity in Virtual Education of Medical Students - Rahele Gharibnavaz; Elham Fariborzi; Hossien karimi Moonaghi; Mahmoud Ghorbani (Mashhad University of Medical Sciences, 2023)
Background: The lack of familiarity with netiquette or social etiquette in virtual space overshadows teaching and learning processes. Learning netiquette (virtual ethics) is one of the ways to deal with the negative effects of education in the virtual space in universities to improve the effectiveness of education. The purpose of this research was to familiarize with Netiquette and examine its necessity in the virtual education of medical students.Method: Articles using Persian keywords and their Latin equivalents, which include "virtual education" "Netiquette" "virtual space" and "electronic learning" separately and combined in internal and external sites: Scopus, Magiran, Irandoc, SID, Noormags, PubMed as well as Google Scholar search engine were searched regardless of the time limit.Results: Commitments in cyberspace are in the form of virtual commitments that are often anonymous and unrealistic, they weaken the context of moral and educational commitments in users and make the requirements of adhering to these commitments lighter.Conclusion: The lack of familiarity with netiquette and virtual professionalism causes defects in the two critical elements of the educational system (teacher and student) the emergence of misunderstandings and sometimes behaviors far from the dignity of each of them, as one of the critical issues in this research.